E0043 Effects of simvastatin on angiogenesis and the expression of Ang1 after myocardial infarction in rats. (17th November 2010) - Quan, He; Shu, Qin; Kanghua, Ma; Suxin, Luo; Xiaogang, Zhang
Abstract : Objective: To investigate the effects of simvastatin on myocardial angiogenesis and the expression of angiopoietin-1 after experimental myocardial infarction (MI) in rats. Methods: 60 healthy adult SD rats were randomly divided into the sham operated group, the control group, low dose of simvastatin (1 mg·kg −1 ·d −1 ) group, medium dose of simvastatin (10 mg·kg −1 ·d −1 ) group, high dose of simvastatin (40 mg·kg −1 ·d −1 ) group. Left anterior descending coronary underwent permanent occlusion to establish the MI model. Rats were administered simvastatin respectively via oral gavage for four consecutive weeks starting at the next day. Density of new microvessels in the ischaemic area, LVMI, protein and mRNA expression of Ang-1 were detected 4 weeks after operation. Results: (1) Compared with the control group, the Density of new microvessels in low and medium dose of simvastatin group increased significantly (p<0.05); and those did not changed significantly in high dose of simvastatin group (p>0.05) (2) LVMI in low and medium dose of simvastatin group decreased significantly compared with that in control group (p<0.05), and further decreased in high dose of simvastatin group. (3) The protein and mRNA expression of Ang-1 in all simvastatin group increased significantly compared with that in control group (p<0.05). Conclusion: (1) Low and medium dose of simvastatin can stimulate myocardial angiogenesis after MI, wherase high dose of simvastatin have no pro-angiogenic effect. (2) the pro-angiogenic effect of simvastatin may be associated with upregulated expression of Ang-1.